Demographic and Clinical Factors Associated With Nonsurgical Osteoarthritis Treatment Among Patients in Outpatient Clinics. Issue 8 (5th July 2018) - Abbate, Lauren M.; Jeffreys, Amy S.; Coffman, Cynthia J.; Schwartz, Todd A.; Arbeeva, Liubov; Callahan, Leigh F.; Negbenebor, Nicole A.; Kohrt, Wendy M.; Schwartz, Robert S.; Vina, Ernest; Allen, Kelli D.
Abstract : Objective: To identify patient demographic and clinical characteristics associated with osteoarthritis (OA) treatment use. Methods: This was a secondary data analysis of 3 clinical trials among patients with hip or knee OA conducted in Duke Primary Care practices, the Durham Veterans Affairs (VA) Health Care System, and the University of North Carolina–Chapel Hill (UNC). At baseline, participants reported sociodemographic characteristics, OA‐related pain and function, and OA treatment use, including oral analgesics, topical creams, joint injections, and physical therapy. Separate, multivariable logistic models (adjusted for clustering of clinics and providers for the Duke and VA cohorts) were used to estimate odds ratios (ORs) and 95% confidence intervals (95% CIs) for the associations between participant characteristics and each type of OA treatment. Results: Oral analgesic use was reported by 70–82% of participants across the 3 cohorts. Physical therapy, knee injections, and topical creams were used by 39–52%, 55–60%, and 25–39% of Duke, VA, and UNC participants, respectively. In multivariable models, worse pain, stiffness, and function, per 5‐unit increase, were associated with greater odds of using any oral analgesic for the cohorts from Duke (OR 1.18 [95% CI 1.08–1.28]) and UNC (OR 1.14 [95% CI 1.05–1.24]), but not for the VA cohort (OR 1.04 [95% CI 0.95–1.14]). For all 3 cohorts, nonwhites had higher odds of using topical creams compared to whites. Conclusion: Results suggest potential underutilization of therapies other than oral analgesics. Patient characteristics may affect OA treatment use, and understanding the relationship between these factors and OA treatment preferences may improve adherence to OA treatment guidelines.